The Interplay of the Angiotensin Receptor Blockers and Hematological Abnormalities: Insights and Implications - Ghada M Ahmed; Alassaf, Fawaz A.; Abed, Mohammed N. (Journal of Ayub Medical College Abbottabad, 2024)
Antihypertensive medications known as angiotensin receptor blockers (ARBs) have become increasingly popular for treating conditions beyond hypertension. The reason for this widespread use is mainly due to their renoprotective and cardioprotective properties in patients with congestive heart failure and diabetes mellitus. There have been conflicting studies on the relationship between ARBs and hematological abnormalities. Using the supplied search terms, we carried out a thorough search for relevant papers written in English and published before July 2023. All of the studies that met the selection criteria were searched for on PubMed, Cochrane Library, and Google Scholar. Based on the examined data from the searched literatures, it has been demonstrated that angiotensin II is essential for stimulation of erythropoiesis and inhibition of it by drugs such as ARBs can lower hematocrit levels, leading to anemia. Accordingly, dose reduction or stopping administration of ARBs could be a choice for correction of anemia. However, such decision is based on the clinical situation and the requirements for other management options.